Penyelesaian Tindak Pidana Narkotika Melalui Restorative Justice: Studi Kasus di Kejaksaan Tinggi Sulawesi Tengah - Anisa; Vivi Nur Qalbi; Andi Nurul Isnawidiawinarti Achmad; Keyu Zulkarnain Arif (CV Rewang Rencang, 2025)
Restorative justice in the resolution of narcotics crimes in Indonesia is a more humane alternative to the retributive approach. This approach focuses on restoring relationships between perpetrators, victims, and the community, involving mediation and consensus-based resolutions. This study analyzes the implementation of restorative justice at the Central Sulawesi High Prosecutor's Office, which is expected to provide substantial justice for drug offenders who act as users rather than dealers. The results of the study indicate that this implementation is effective but faces challenges in terms of rehabilitation facilities and community acceptance.